ESTIMATION OF THERMODYNAMIC PARAMETERS OF POLYSTYRENE-N-HYDROCARBONS SYSTEMS USING INVERSE GAS-CHROMATOGRAPHY - OZDEMIR, E; COSKUN, M; ACIKSES, A (Marcel Dekker Inc, 1991)
Thermodynamic parameters like partial molar free energy, Flory-Huggins interaction parameter, weight fraction activity coefficient and molar heats of polystyrene- n}hydrocarbons systems were determined by using inverse gas chromatography technique. The results obtained showed similarity with that of polymer-non solvent systems.
Keywords: Liquid-Chromatography; Molecular-Probes; Polymers; Temperatures